Mechanical licensing of the NLRP3 inflammasome in hypertensive vasculature: Integrin mechanotransduction and cytoskeletal control of vascular inflammation - Noof Abdulrahman Alrabiah; Safwan Abid Al-hameed Suliman; Lashin S. Ali; Waseem Ali Hasan; Amany Said Sallam; Rabab S. Hamad; Etedal Ahmed A. Ibrahim; Eman Hamza; Nesreen Elsayed Morsy; Ahmed Shata; Hanan Eissa; Alshaimaa A. Farrag; et al. (Tissue and Cell, 2027)

Dysregulation of circ-SMARCA5, circ-RHOT1, and HNF1A and the association of HNF1A polymorphisms with hepatocellular carcinoma - Basma A. Ibrahim; Basma S. Elsayed; Mohamed Abdelaziz Gendia; Manar Moustafa; Ansam M. Z. El Desoky (Molecular Biology Reports, 2026)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

Pharmaceutical Innovation in Salivary Biomarker Research: Transforming Oral Healthcare through Nanotechnology and Point-of-Care Systems: A Narrative Review - Akram N. Salah; Ahmed E. Elesawy; Mohamed Bakr Zaki; Ahmed I. Abulsoud; Gharieb S. El-Sayyad; Wagiha S. Elkalla; Nehal I. Rizk; Osama A. Mohammed; Hend H. Mohamed; Nourhan H. Elshami; Asmaa A. Ibrahim; Salma W. Elsayed; et al. (Journal of Pharmaceutical Innovation, 2026)

Dietary lemon essential oil mitigates metalaxyl-induced oxidative stress, hematological disruptions, and immunotoxicity in Nile tilapia (Oreochromis niloticus) with associated changes in splenic MAPK-and caspase-related gene expression - Elsayed M. Younis; Afaf N. Abdel Rahman; Tarek Khamis; Abdelwahab A. Abdelwarith; Simon J. Davies; Faozi S. Shamlol; Nehal A. Younis; Rowida E. Ibrahim; Gehad E. Elshopakey (Research in Veterinary Science, 2026)

Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Adenosine A₂A receptor as a dual-acting molecular switch: Glial morphological changes and neurovascular tissue remodeling in neuroinflammation and neurodegeneration - Heba Ibrahim Abd El-Moaty; Ahmed Sameh; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Norah Suliman Alsoqih; Alshaimaa A. Farrag; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; et al. (Tissue and Cell, 2026)

FOXO3a-mediated structural and cellular remodeling in liver tissue: Implications for apoptosis and homeostasis - Heba Ibrahim Abd El-Moaty; Sameh Saber; Rabab S. Hamad; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Simona Cavalu; Hanan Eissa; Attalla F. El-kott; Sally Negm; Mohammed A. AlShehri; Mohamed A.M. Ali; Waseem Ali Hasan; et al. (Tissue and Cell, 2026)

Molecularly diverse lonazolac-inspired pyrazole-cyanopyridin-2-one conjugates: design, synthesis, in vitro, in vivo and in silico studies as multi-target anti-inflammatory agents - Marwa A. Aziz; Azizah M. Malebari; Tarek S. Ibrahim; Mohamed F. Radwan; Deiaa E. Elsayed Abouzed; Rasha M. Allam; Majed Alharbi; Ahdab N. Khayyat; Gamal El-Din A. Abuo-Rahma; Mamdouh F. A. Mohamed (Molecular Diversity, 2026)

A new cadinane-type sesquiterpenoid glucoside from Centaurea alexandrina - Ibrahim A. Saleh; Wael M. Elsayed; Taha A. Hussien; Abdelsamed I. Elshamy; Tarik A. Mohamed; Mohamed-Elamir F. Hegazy (Natural Product Research, 2026)

Investigation of the Antibacterial Effectiveness of Hybrid Recombinant Bacteriocins Circular Enterocin and Pyocin L1 Derived from Pseudomonas aeruginosa and Enterococcus faecalis - Lina Jamil Abdel-Hafez; Mohamed Salah Basiouny; Islam Yousif Mostafa; Rehab Moustafa; Khaled Abuelhaded; Haytham Mohamed Abd-Elhalim; Abanoub A. S. Shaker; Hassan Elsayed; Olfat Salem; Amir Mahfouz Mokhtar Sarguos; Ahmed Hassan Ibrahim Faraag (Biochemical Genetics, 2026)

Pimenta racemosa extract ameliorates chemically induced ulcerative colitis in rats by suppressing inflammation and oxidative stress - Haitham A. Ibrahim; Fathia S. Elshaarawy; Mohamed I. S. Abd-elhady; Wafaa Hamdy; Merhan E. Ali; Asmaa A. Ahmed; Elsayed K. El-Sayed (Inflammopharmacology, 2026)
Pimenta racemosa ( P. racemosa ) tree leaves are used in traditional medicine to alleviate flatulence and gastrointestinal disorders. Ulcerative colitis (UC) is a gastrointestinal inflammatory disease with well-known inflammatory and immunoregulatory pathological features. The complexity of the disease requires multi-targeted treatment. Because of their relative safety and effectiveness, natural products can be utilized as adjunct and alternative agents to conventional UC treatment. So , the present work aimed to isolate phenolic constituents of the plant’s 80% aqueous methanol extract (AME) and evaluate its protective effect on acetic acid-induced ulcerative colitis (UC) in rats. The defatted AME was chromatographed, and structures of the isolated compounds were elucidated using UV, NMR spectroscopy and HPLC–ESI–MS analysis. Induction of ulcerative colitis was done using Acetic acid, the protective effect against ulcerative colitis was supported by histopathological and immunohistochemical examinations. The isolated compounds are Kaempferol 3- O - β -D-glucopyranoside (kaempferol 3- O -glucoside) or (Astragalin) (1) , quercetin 3- O-β -D-glucopyranoside (Isoquercetrin) (2) , Quercetin (3) , Catechin (4) , quercetin 3- O-α- L-rhamnospyranoside (Quercetrin) (5) . The AME of P. racemosa significantly alleviated the UC by decreasing the disease activity index and Wallace score. Additionally, GSH, CAT, and SOD were increased, and MDA was decreased, suggesting AME’s antioxidant activity. The decreased levels of WBCs, neutrophils, TNF-α, IL-1β, IL-6, MPO, and NF-κB p65 support the AME’s anti-inflammatory properties. The highest activity was recorded for the dose of 1000 mg/kg. These findings were in harmony with the histopathological examination and the Alcian Blue staining for mucin content. The current study revealed that the AME of P. racemosa has protective activities against UC in rats via its antioxidant and anti-inflammatory properties may be attributed to its phenolic profile.

Uterine and ovarian hemodynamics assessment of Camelus dromedarius with hormonal alterations and anatomical and histological architecture - Elshymaa A. Abdelnaby; Asmaa M. Ibrahium; Aya M. Mekkawy; Ibrahim A. Emam; Alaa H. Elsayed (Veterinary Research Communications, 2026)

Correction: Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

Impact of Trichoderma, abscisic acid and polyamines on resistance tomato cultivars against M. incognita infection - Ibrahim A. Adss; Shokry R. Bayoumi; Hesham M. Heikal; Sherien E. Sobhy; Ahmed A. Saleh; Elsayed E. Hafez (Molecular Biology Reports, 2025)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

Bioprotective potential of biosynthesized copper oxide nanoparticles and copper phosphite against Alternaria-solani-induced leaf spot in pepper plants - Mohamed S. Attia; Mohamed H. Moustafa; Amr H. Hashem; Salah M. Elsayed; Abeer S. Aloufi; Ismail Mostafa Ismail Abdelaleem; Karim A. Alshahed; Abdelrhman S. Ismail; Abdelrhman M. Ibrahim; Mostafa A. Abdel-Maksoud; Abdulaziz Alamri; Hossam Ebaid; et al. (Antonie van Leeuwenhoek, 2025)

Neuroprotective activity of Colocasia esculenta (L.) Schott leaves against monosodium glutamate-induced excitotoxicity in rats: phytochemical and molecular docking study - Heba T. Khazaal; Elsayed K. El-Sayed; Yara E. Mansour; Reham R. Ibrahim; Mokhtar Bishr; Rabab A. El Dib; Hesham S. M. Soliman (Natural Product Research, 2025)

Behavioral and neurological responses of Oreochromis niloticus to chronic cyclic hypoxia: mechanistic insights into hypoxia-responsive genes, pro-inflammatory and apoptotic pathways: role of camel whey protein hydrolysate - Amany Abdel-Rahman Mohamed; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Rowida E. Ibrahim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Abd Elhakeem El-Murr; Simon J. Davies; Yasmina M. Abd-Elhakim (Veterinary Research Communications, 2025)

Mitigating potential of Malva parviflora leaves against Polyram DF (dry flowable) toxicity in Nile tilapia: immune/apoptotic markers, biochemical, antioxidant, and histopathological insights - Elsayed M. Younis; Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Engy Mohamed Mohamed Yassin; Kholoud A. Alhallag; Mohammed S. Sobh; Mohamed Shaalan; Tarek Khamis; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Investigating the impact of camel whey protein hydrolysate on cyp1a1 and keap1/nrf2 expression in hypoxic stress-affected liver tissue of Oreochromis niloticus - Amany Abdel-Rahman Mohamed; Afaf A. Kishta; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Yasmina M. Abd-Elhakim; Rowida E. Ibrahim; Mohamed M. M. Metwally; Tarek Khamis; Ali Osman; Simon J. Davies; Mohamed A. Elbealy (Journal of Comparative Physiology B, 2025)

The potential of bone marrow derived mesenchymal stem cells in treating cisplatin induced sensorineural hearing loss in a guinea pig animal model - Mohamed Hassan Ali Elsayed Abdelwahed; Mohamed Hussien Badreldin; Ibrahim Hassan Ibrahim; Reham Farouk Zittoon; Rania A. Galhom; Sally S. Mohammed; Yehia Mohamed Ashry (Tissue and Cell, 2025)

Alleviative potential of dietary essential oils against nickel toxicity triggers neurobehavioral abnormalities, biochemical dysfunction, and histopathological alterations in Nile tilapia - Shaimaa A. A. Ahmed; Ali Adel Ali Ahmed; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Mai Farag Saad; Simon J. Davies; Rowida E. Ibrahim; Asmaa Edrees (Veterinary Research Communications, 2025)

Ameliorative potential of Populus alba leaf powder against hexaflumuron exposure in Nile tilapia: immune-antioxidant, biochemical, histological, and transcriptomic analysis - Rowida E. Ibrahim; Mohamed F. M. Farag; Mohammed S. Sobh; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Shefaa M. Bazeed; Aya Elgamal; Tarek Khamis; Simon J. Davies; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2025)

Carbonate alkalinity induces stress responses and renal and metabolic disorders in Nile tilapia: mitigation by camel whey protein hydrolysate diet - Rowida E. Ibrahim; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Amany Abdel-Rahman Mohamed; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Yasmina M. Abd-Elhakim (Fish Physiology and Biochemistry, 2025)

Adaptation and development plans of the Egyptian ports under the impacts of climate change - Ahmed A. Romya; Ahmed Elsayed Elkut; Asmaa A. Abu Zed; Hossam M. Moghazy; Maysara Khairy El-Tahhan; Akram Soliman; Mona G. Ibrahim; Moheb Iskander; Mahmoud Sharaan (Ocean & Coastal Management, 2025)

Dietary Prunus armeniaca augments antioxidant-immune-capacity, absorptive function, and growth and upregulates nutrient transporters and immune-regulatory genes of Oreochromis niloticus - Afaf N. Abdel Rahman; Sara T. Elazab; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2025)

Potential Impact of SOD2 (rs4880; p.Val16Ala) Variant with the Susceptibility for Childhood Bronchial Asthma - Nahla H. Anber; Hanaa Elsayed Ahmed Shahin; Heba K. Badawy; Enas A. Oraby; Sameh A. Mohammed; Esraa Ibrahim A. Shaaban; Zeinab Rizk Attia; Shereen Mohamed; Mona Farag Shabana; Mohamed Adel El‑Eshmawy; Riham Elsayed; Afaf M. Elsaid; et al. (Biochemical Genetics, 2025)

Potential of using kidney bean (Phaseolus vulgaris L) protein hydrolysate as a plant protein supplement in Nile tilapia (Oreochromis niloticus) diets: effects on growth, hematology, histology, and blood biochemical parameters - Shimaa A. Amer; Rowida E. Ibrahim; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Ali Osman; Simon J. Davies; Medhat S. Shakweer (Aquaculture International, 2025)

New Ionic Liquid Forms of Antituberculosis Drug Combinations for Optimized Stability and Dissolution - Hanan E. Rasmy; Sara A. Abouelmagd; Elsayed A. Ibrahim (AAPS PharmSciTech, 2025)
Isoniazid (INH) and rifampicin (RIF) are the two main drugs used for the management of tuberculosis. They are often used as a fixed drug combination, but their delivery is challenged by suboptimal solubility and physical instability. This study explores the potential of active pharmaceutical ingredient-ionic liquids (API-ILs) to improve the physicochemical and pharmaceutical properties of INH and RIF. Antitubercular drugs, INH, or RIF, were paired with different counter ions (ascorbic acid (AsA), citric acid (CA), tartaric acid (TA), benzoic acid (BA), salicylic acid (SA), and p-amino salicylic acid (PAS)) using the solvent evaporation method. INH and RIF API-ILs were formed successfully using AsA and CA counter ions. IL formation was examined and analyzed using Fourier transform infrared (FTIR) spectroscopy, x-ray powder diffraction (XRPD), and polarized optical microscopy (POM). XRPD and POM confirmed their amorphous nature, while FTIR analysis demonstrated the contribution of hydrogen bonding to IL formation. IL formation enhanced the storage stability of the INH + RIF mixture in the presence of CA. Moreover, RIF-CA IL significantly increased the rate and extent of RIF dissolution. An effect that is unattainable with the RIF/CA physical mixture. Thus, API-IL formation not only enhances RIF dissolution but also facilitates the preparation of stable, compatible INH-RIF combinations. Graphical Abstract

Retraction notice to “The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological/immunohistochemical investigation of gills” [Aquaculture 584 (2024) 740639] - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2025)

Lead toxicity in African catfish: Promising role of magnetite nanogel against etho-neurological alterations, antioxidant suppression, gene toxicity, and histopathological/ immunohistochemical disruptions - Afaf N. Abdel Rahman; Heba H. Mahboub; Rasha M.M. Ezz-Eldin; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Tarek Khamis; Enas K. Aziz; Walaa A.A. Basha; Ibrahim Elmaghraby; Simon J. Davies; Sameh H. Ismail; Yasmin A. Reyad (Aquaculture, 2025)

Antagonistic Effect of Zinc Oxide Nanoparticles Dietary Supplementation Against Chronic Copper Waterborne Exposure on Growth, Behavioral, Biochemical, and Gene Expression Alterations of African Catfish, Clarias gariepinus (Burchell, 1822) - Shaimaa A. A. Ahmed; Rowida E. Ibrahim; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Khaled Yehia Faroh; Samar A. El Gamal; Shereen Badr; Tarek Khamis; Abdallah Tageldein Mansour; Simon J. Davies; Mohamed ElHady (Biological Trace Element Research, 2024)

Camel whey protein hydrolysate diet mitigates alkaline stress–induced biochemical disorders and restores the target of rapamycin, MAPK pathway, and autophagy-related gene expression in Nile tilapia - Rowida E. Ibrahim; Gehad E. Elshopakey; Mohamed Y. M. Aly; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Yasmina M. Abd-Elhakim; Tarek Khamis; Ali Osman; Mohamed M. M. Metwally; Simon J. Davies; Amany Abdel-Rahman Mohamed (Aquaculture International, 2024)

Using moringa (Moringa oleifera) seed protein hydrolysate as a dietary protein supplement modulates hemato-biochemical indices, antioxidant response, and tissue histo-morphology of Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Shimaa A. Amer; Nasreddin R. Rhouma; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Heba M. Abdel-Ghany; Gehad E. Elshobaky; Mahmoud M. El-Saber; Ali Osman; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture International, 2024)

Efficacy of the dietary Malva parviflora leaves in modulating immune-antioxidant functions, resistance to Candida albicans and Streptococcus agalactiae infection, digestive/absorptive capacity, and growth of Nile tilapia (Oreochromis niloticus) - Afaf N. Abdel Rahman; Yasmin A. Reyad; Gehad E. Elshopakey; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Nehal Abd EL-Mageed; Afaf A. Kishta; Asmaa Yaseen; Simon J. Davies; Rowida E. Ibrahim (Aquaculture International, 2024)

Marine Smenospongia extract mitigated co-infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia: insights into promoting growth performance, immune, antioxidant and autophagy defenses, and suppression of endoplasmic reticulum stress-related genes - Doaa Ibrahim; Ioan Pet; Reham G. A. Anter; Abdelwahab A. Abdelwarith; Mona Mohammed I. Abdel Rahman; Basant M. Shafik; Elsayed M. Younis; Asmaa Basiony; Shimaa A. E. Atwa; Aya Sh. Metwally; Heba A. Tolba; Mirela Ahmadi; et al. (Frontiers in Marine Science, 2024)
Identifying novel natural sources from the marine environment with unique immunomodulatory and antioxidant efficacies is of interest in intensive fish farming. In this sense, marine sponge extract derived from Smenospongia (SS-extract) was tested for its potential anti-inflammatory, antioxidant and antimicrobial activities during the concurrent infection with Trichodina sp. and Flavobacterium columnare in Nile tilapia. A total of 625 Nile tilapia fingerlings were distributed into five groups: the control group (with no additives) and four groups fed the control diet fortified with SS-extract at 50, 100, 150, and 200 mg/kg, respectively, for 60 days. The parasitic challenge with Trichodina sp was done at the endpoint of the feeding trial and at 7 days post-infection (dpi); the fish were coinfected with F. columnare . A significant improvement in growth-related parameters of Nile tilapia was detected in the groups that received SS-extract at the levels of 150 and 200 mg/kg. The scavenging ability for free radicals (2,2′-azino-bis-3-ethylbenzthiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH)) was maximized with higher SS-extract supplementation levels. Simultaneously, the antioxidant defense of the Nile tilapia fed 150 and 200 mg/kg was augmented with a decline in oxidation-associated indicators [reactive oxygen species (ROS), hydrogen peroxide (H 2 O 2 ), and malondialdehyde (MDA)]. The higher concentrations of SS-extract in the feed potentiated the immune response of Nile tilapia before infection and even after coinfection and was paralleled by a subsiding in the exaggerated inflammatory response after concurrent infection. Concurrently, the mRNA expression of autophagy-encountered genes ( Atg5 and 12, LC3-II and BCLN1 ) had its highest expression in the fish fed the 200 mg/kg diet with the lowest expression of the mTOR gene in the same fish. The lowest infection intensity and rate and mucus score were displayed in fish fed 200 mg/kg SS-extract at 20 dpi. Interestingly, higher levels of SS-extract triggered antimicrobial peptides (upregulation of Hepcidin and β-defensin-1). In contrast, excessive expression of endoplasmic reticulum genes ( atf4 , JAK1 , PERK , and eif2α ) in the control infected group was downregulated by 200 mg/kg of SS-extract. The quantification of F. columnare indicated that columnaris coinfection severity displayed its lowest rate in the group supplemented with 200 mg/kg of SS-extract. In conclusion, a strategic siting based on fortification of the diet of Nile tilapia with SS-extract was elucidated to reinforce its immune and antioxidant defenses during a concurrent infection.

The role of marine bacteria in modulating the environmental impact of heavy metals, microplastics, and pesticides: a comprehensive review - Islam I. Teiba; Emad H. El-Bilawy; Ibrahim A. Abouelsaad; Akram Ismael Shehata; Mayada Alhoshy; Yusuf Jibril Habib; Nermeen M. Abu-Elala; Nagwa EL-Khateeb; Elsayed B. Belal; Warda A. M. Hussain (Environmental Science and Pollution Research, 2024)

Coupling several spectral manipulations with isosbestic approach to resolve overlapped spectra for concurrent analysis of lamivudine/tenofovir combination: Evaluating environmental sustainability - Bardees Abdelmonem Khashaba; Elsayed A. Ibrahim; Ghada M. Hadad; Michael Gamal Fawzy (Sustainable Chemistry and Pharmacy, 2024)

Hexaflumuron insecticide exposure induces behavior alterations, hemato-biochemical disorders, antioxidant-immune dysfunction, and histopathological alterations in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Basma A. Elshafey; Simon J. Davies; Afaf N. Abdel Rahman (Veterinary Research Communications, 2024)

The alleviative effect of Bacillus subtilis-supplemented diet against Vibrio cholerae infection in Nile tilapia (Oreochromis niloticus) - Omnia A. Elewasy; Amira S. Elrafie; Neveen A. Rasheed; Sara H. Adli; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Rowida E. Ibrahim (Veterinary Research Communications, 2024)

The therapeutic role of Azadirachta indica leaves ethanolic extract against detrimental effects of Aeromonas veronii infection in Nile tilapia, Oreochromis niloticus - Hesham A. Khalifa; Esraa Sharawy; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Rowida E. Ibrahim; Shimaa A. Amer; Simon J. Davies; Azza M. A. Abo-Elmaaty (Fish Physiology and Biochemistry, 2024)

Use of remote sensing, spatial and geophysical modeling, and real recharging capabilities to identify suitable areas for groundwater exploitation in dry coastal areas - Hossam H. Elewa; Ahmed M. Nosair; Amin Ibrahim; Martina Zelenakova; Katarzyna Pietrucha-Urbanik; Hazem M. Habib; Nermeen A. Abdel Moneam; Rania M. Ragab; Elsayed M. Ramadan (Journal of Environmental Management, 2024)

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

Potential inhibitory effect of geraniol isolated from lemongrass ( Cymbopogon commutatus Stapf) on tilmicosin-induced oxidative stress in cardiac tissue - Rebai Ben Ammar; Sarah Abdulaziz Alamer; Maged Elsayed Mohamed; Duaa Althumairy; Saeed Y. Al-Ramadan; Manal Alfwuaires; Nancy S. Younis; Thnaian A. Althnaian; Ibrahim R. I. H.; Peramaiyan Rajendran (Natural Product Research, 2024)

Retracted: The anti-parasitic effect of Melaleuca alternifolia oil against gills monogeneans (Dactylogyrus spp) infestation of Clarias gariepinus: Hematology, immune response, and histopathological / immunohistochemical investigation of gills - Afaf N. Abdel Rahman; Mohamed F.M. Farag; Alshimaa A. Khalil; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Shimaa R. Masoud; Shefaa M. Bazeed; Aya Elgamal; Refaat Ras; Simon J. Davies; Rowida E. Ibrahim; Amany M. Abd El-Ghany (Aquaculture, 2024)

A comparative novel green reversed-phase high-performance liquid chromatography method for simultaneous determination of ivabradine and carvedilol in tablets and human plasma using UV and fluorescence detectors - Ethar A. Rashad; Samar S. Elsayed; Jenny Jeehan M. Nasr; Fawzia A. Ibrahim (Sustainable Chemistry and Pharmacy, 2024)

Retraction Note: Effects of genistein on pentylenetetrazole-induced behavioral and neurochemical deficits in ovariectomized rats - Amr A. Elsayed; Esther T. Menze; Mariane G. Tadros; Bassant M. M. Ibrahim; Nagwa A. Sabri; Amani E. Khalifa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Use of moringa protein hydrolysate as a fishmeal replacer in diet of Oreochromis niloticus: Effects on growth, digestive enzymes, protein transporters and immune status - Shimaa A. Amer; Afaf N. Abdel Rahman; Mohamed ElHady; Ali Osman; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Amr A. Moustafa; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquaculture, 2024)

The anti-bacterial efficacy of zinc oxide nanoparticles synthesized by Nelumbo nucifera leaves against Clostridium perfringes challenge in Oreochromis niloticus - Rowida E. Ibrahim; Moustafa M.S. Fouda; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Gamal A. Salem; Ahmed Asaid Elkady; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Aquaculture, 2024)

Nelumbo nucifera synthesized selenium nanoparticles modulate the immune-antioxidants, biochemical indices, and pro/anti-inflammatory cytokines pathways in Oreochromis niloticus infected with Aeromonas veronii - Rowida E. Ibrahim; Gehad Elshobaky; Mohamed ElHady; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nasreddin R. Rhouma; Suzan K. Murad; Engy Mohamed Mohamed Yassin; Tarek Khamis; Sameh H. Ismail; Simon J. Davies; Afaf N. Abdel Rahman (Fish & Shellfish Immunology, 2024)

Novel green HPTLC and organic solvent-free micellar LC methods for the simultaneous determination of Ozenoxacin and benzoic acid; greenness assessment and applications - Adel Ehab Ibrahim; Mohamed Farouk Taher; Alaa El Gindy; Elsayed A. Ibrahim (Sustainable Chemistry and Pharmacy, 2023)

Potential role of dietary Boswellia serrata resin against mancozeb fungicide-induced immune-antioxidant suppression, histopathological alterations, and genotoxicity in Nile tilapia, Oreochromis niloticus - Afaf N. Abdel Rahman; Dalia E. Altohamy; Gehad E. Elshopakey; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Nora M. Elseddawy; Aya Elgamal; Shefaa M. Bazeed; Tarek Khamis; Simon J. Davies; Rowida E. Ibrahim (Aquatic Toxicology, 2023)

Kidney bean protein hydrolysate as a fish meal replacer: Effects on growth, digestive enzymes, metabolic functions, immune-antioxidant parameters and their related gene expression, intestinal and muscular gene expression - Rowida E. Ibrahim; Samar A. Tolba; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Shimaa I. Shalaby; Ali Osman; Tarek Khamis; Mohamed A. Eissa; Simon J. Davies; Shimaa A. Amer (Aquaculture, 2023)

Neem seed protein hydrolysate as a fishmeal substitute in Nile tilapia: Effects on antioxidant/immune pathway, growth, amino acid transporters-related gene expression, and Aeromonas veronii resistance - Afaf N. Abdel Rahman; Shimaa A. Amer; Shimaa R. Masoud; Mahmoud M. El-Saber; Ali Osman; Elsayed M. Younis; Abdelwahab A. Abdelwarith; Simon J. Davies; Tarek Khamis; Rowida E. Ibrahim (Aquaculture, 2023)

Acute mancozeb-fungicide exposure induces neuro-ethology disruption, health disorders, and immune-oxidative dysfunction in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Mohamed A. Elbealy; Gamal A. Salem; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Ahmed Asaid Elkady; Simon J. Davies; Afaf N. Abdel Rahman (Aquatic Toxicology, 2023)

Impact of Streptococcus agalactiae Challenge on Immune Response, Antioxidant Status and Hepatorenal Indices of Nile Tilapia: The Palliative Role of Chitosan White Poplar Nanocapsule - Afaf N. Abdel Rahman; Sameh H. Ismail; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Samah S. Khalil; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Simon J. Davies; Rowida E. Ibrahim (Fishes, 2023)
A new insight into the synthesis of the herbal plant (White poplar, Poplus alba) leave extract using chitosan nanocapsule was studied. The in vitro antibacterial activity of chitosan white poplar nanocapsule (CWPNC) against Streptococcus agalactiae (S. agalactiae) was determined. About 120 fish were categorized for 7 days into four groups. The first and second (CWPNC) groups were treated with 0 mg/L and 3 mg/L CWPNC in the water, respectively, without being challenged; the first group was a control. The third (S. agalactiae) and fourth (CWPNC + S. agalactiae) groups were treated with 0 and 3 mg/L CWPNC, respectively, and challenged with S. agalactiae (0.5 × 107 CFU/mL). The obtained results revealed that CWPNC had an in vitro antibacterial activity against S. agalactiae. Moreover, S. agalactiae infection caused a significant elevation (p

Resveratrol and Dulaglutide ameliorate adiposity and liver dysfunction in rats with diet-induced metabolic syndrome: Role of SIRT-1 / adipokines / PPARγ and IGF-1 - Hanan Abdel Moneam A. Shamardl; Noha A. Ibrahim; Dina H. Merzeban; Azza M. Elamir; Rehab M. Golam; Asmaa M. Elsayed (DARU Journal of Pharmaceutical Sciences, 2023)
Background Adiposity and non-alcoholic fatty liver disease (NAFLD) are common characteristics of metabolic syndrome (MS). Understanding the underlying pathogenesis is crucial for the development of new remedies. Resveratrol controls obesity and glycemic disorders in patients with MS. Objectives This study aimed to evaluate the effect of resveratrol and dulaglutide on adipose tissues and liver in rats with MS, declaring their possible mechanisms. Methods Rats allocated as Control, MS (induced by a high fat/ high sucrose diet for eight weeks), MS + Resveratrol (30 mg/kg/day orally), and MS + Dulaglutide (0.6 mg/kg twice weekly SC); drugs administration was in the last four weeks. Serum biochemical measurements were done. Liver and visceral fat were processed for biochemistry, histopathology, and immunohistochemistry. Results MS results demonstrated significantly increased systolic and diastolic blood pressure, anthropometric measurements, serum levels of alanine aminotransferase (ALT), glycemic indices, and lipids with decreased HDL-C. Tissue levels of leptin, malondialdehyde (MDA), and TNF-α reactivity significantly increased. Expression of adiponectin, PPARγ, and insulin growth factor-1 (IGF-1) decreased. Also, Western blotting mRNA gene expression of liver SIRT-1 was down-regulated. Resveratrol and dulaglutide significantly and effectively reversed MS complexity, ameliorating all findings, particularly NAFLD and adiposity-induced inflammation. Resveratrol significantly appears superior to dulaglutide regarding the effects on hemodynamics, lipids, adipokines, IGF-1 levels, and adipocyte size. Parallel, dulaglutide has more influence on glycemic control. Conclusion Protective effects of the drugs may be through correlations between SIRT-1/adipokines/IGF-1 and PPARγ, improving the cross-talk between insulin resistance, obesity markers, liver dysfunction, and TNF-α. Promising multi-beneficial therapies of resveratrol or dulaglutide in MS are recommended clinically for this purpose. Graphical Abstract Showing the Experimental Design

Effects of dietary supplementation of chromium methionine chelate on growth performance, oxidative stress, hematological indices, and carcass traits of broiler chickens - Ibrahim M. I. Youssef; Ibrahim M. I. Abdo; Hassan F. A. Elsukkary; Magdy F. El-Kady; Magdy Elsayed (Tropical Animal Health and Production, 2022)
This study was conducted to evaluate the dietary effects of chromium methionine (Cr-Meth) chelate on growth performance, oxidative stress parameters, blood biochemistry, and carcass traits of broiler chickens. An experiment was conducted on 34,000 1-day-old straight-run broiler chicks (Indian River; 42.0 ± 0.03) at a commercial farm. The chicks were divided randomly into 3 groups; the first group contained 17,000 birds, which used as a control, whereas the second and third groups consisted of 7000 and 10,000 birds, respectively, with 5 replicates per group. A completely randomized design was used. The birds were fed the experimental diets containing graded levels of Cr-Meth chelate: 0 (control), 50, and 100 g/ton. This compound consisted of chromium (0.4%) chelated with methionine, and it supply the diets with 200 and 400 ppb Cr for the used levels of 50 and 100 g/ton feed, respectively. Growth performance indices (body weight, body weight gain, feed intake, and feed conversion ratio) were measured throughout the experiment. At the end of experiment, 10 birds per treatment were slaughtered, and the carcass yield with relative weight of the internal organs was determined. Also, blood samples were taken and analyzed for glutathione peroxidase activity, malondialdehyde, ALT, AST, total protein, albumin, glucose, urea, creatinine, triglycerides, and total cholesterol. It was found that Cr-Meth improved the body weight, weight gain, feed intake, and feed conversion ratio of broilers. Moreover, it reduced the mortality rate of birds. The chelated chromium can alleviate the oxidative status of birds by increasing the plasma glutathione peroxidase activity and reducing the serum malondialdehyde level. It was observed that the effects of 100 g/ton Cr-Meth chelate on performance indices, mortality rate, and oxidative stress parameters were better than that of 50 g/ton inclusion rate. Supplementation of Cr-Meth increased the total protein level, but reduced the glucose, total cholesterol, and triglyceride concentrations in the blood serum. In addition, it increased the carcass yield and reduced the abdominal fat percentage of the birds’ carcass. Therefore, chromium can be included in diets of broilers at a rate of 200 to 400 ppb, and the higher concentration was more effective than the lower one. So, it can be recommended to use Cr-Meth chelate in broiler diets at 100 g/ton to improve the productive performance and reduce the oxidative stress of birds.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Development of activated carbon fibers for removal of organic contaminants - D. S. S. Alkathiri; M. A. Sabri; T. H. Ibrahim; Y. A. ElSayed; F. Jumean (International Journal of Environmental Science and Technology, 2020)

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Biochemical study on modifying role of variants of leptin gene and its receptor on serum leptin levels in breast cancer - Safaa I. Tayel; Alshimaa M. Alhanafy; Solwan M. Ahmed; Abdelmoneim A. Eltorgoman; Ibrahim E. Elsayed (Molecular Biology Reports, 2020)

RETRACTED ARTICLE: Effects of genistein on pentylenetetrazole-induced behavioral and neurochemical deficits in ovariectomized rats - Amr A. Elsayed; Esther T. Menze; Mariane G. Tadros; Bassant M. M. Ibrahim; Nagwa A. Sabri; Amani E. Khalifa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Cytotoxic ceramides from the Red Sea sponge Spheciospongia vagabunda - Enas Elsayed Eltamany; Amany K. Ibrahim; Mohamed M. Radwan; Mahmoud A. ElSohly; Hashim A. Hassanean; Safwat A. Ahmed (Medicinal Chemistry Research, 2015)

The geometric configuration of the newly discovered Abu Deleig sedimentary sub-basin, Central Sudan, using remote sensing, structural analysis, and geophysical survey - Abdalla E. M. Elsheikh; Khalid A. Elsayed Zeinelabdein; Sami O. H. El Khidir; Abdalla E. Ibrahim (Arabian Journal of Geosciences, 2014)

Groundwater balance in the Khor Arbaat basin, Red Sea State, eastern Sudan - Abdalla E. M. Elsheikh; Khalid A. Elsayed Zeielabdein; Ibrahim A. A. Babikir (Hydrogeology Journal, 2009)

The changing patterns of bladder cancer in Egypt over the past 26 years - Ashley S. Felix; Amr S. Soliman; Hussein Khaled; Mohamed S. Zaghloul; Mousumi Banerjee; Manal El-Baradie; Mohamed El-Kalawy; Alaa A. Abd-Elsayed; Kadry Ismail; Ahmed Hablas; Ibrahim A. Seifeldin; Mohamed Ramadan; et al. (Cancer Causes & Control, 2008)